Attitudes, perceptions, and barriers of community pharmacists in Rwanda towards health promotion: a cross sectional study - Amon Nsengimana; Emmanuel Biracyaza; Jean Claude Hategekimana; Jacques Tuyishimire; John Nyiligira; Eugène Rutembesa (BMC, 2022)
Abstract Background The practice of Pharmacists has changed worldwide over the past years. Today, health promotion is better known as an important part of modern pharmacy practice. Involving Community Pharmacists in health promotion is thus considered a valuable option in addressing public health issues. However, the literature on this practice remains unsubstantiated in African countries. In Rwanda, Community Pharmacists are believed to be solely involved in dispensing and very little has been studied about their role in health promotion. Thus, this study aimed to evaluate attitudes, perceptions, and barriers of Community Pharmacists in Rwanda towards their involvement in health promotion. Methods A cross-sectional study was conducted among 236 licensed Community Pharmacists in Rwanda from 23rd January to 23rd June, 2021. A list of all respondents was obtained from Rwanda Food and Drugs Authority. All participants were randomly enrolled. Each community pharmacy was represented by one Pharmacist. We collected data from community pharmacy settings using a self-administered questionnaire made of close and open-ended questions. Statistical analyses were performed using Statistical Packages for Social Sciences (SPSS) version 25. Results Of the 236 respondents, (n = 149, 63.1%) were male and (n = 87,37%) were female. The average age was 38.1 years (SD = 4.3). More than half confirmed that professional curriculum is adequate for offering health promotion services (n = 152, 64.4%).Majority responded that health promotion is part of their responsibility, and they are willing to provide health promotion services (n = 233,98.7%).The statement that "Pharmacists should not be involved in public health activities "was opposed by many (n=174,73.7%).The most sought-after service provided was education to drug misuse (n=211, 89.4%).Three major barriers to provision of health promotion were: lack of coordination with other healthcare professionals(n=106,69%),structure of healthcare system (n=157,67%),and lack of equipment (n=144,61%).Most Pharmacists disagreed with the statement that "patients are not interested in getting health promotion services"(n = 134,57%). Conclusion Though Community Pharmacists faced several challenges that hindered their participation in health promotion, they had positive attitudes towards promoting public health messages. There are several barriers like lack of structure to provide health promotion services that need to be addressed to boost more active participation of Pharmacists in health promotion.